Assessment of soil quality changes following land reclamation at the Martabe Gold Mine, South Tapanuli, Indonesia - ANWAR, SYAIFUL; MANSOR, ASYRAF BIN; HARIS, HAZEEMAN; DHARSONO, MAHYU; LUBIS, ABDILLAH; WAHYUDI, RIZKY; FATHIYA, NIR (Smujo International, 2025)
Abstract. Anwar S, Mansor AB, Haris H, Dharsono M, Lubis A, Wahyudi R, Fathiya N. 2025. Assessment of soil quality changes following land reclamation at the Martabe Gold Mine, South Tapanuli, Indonesia. Asian J Agric 9: 623-628. Mining at Martabe Gold Mine, South Tapanuli, North Sumatra, Indonesia, caused severe soil degradation, requiring effective reclamation. This study evaluated the recovery of soil chemical properties in reclamation sites aged 3, 6, and 10 years compared with adjacent natural forest. Soil samples were analyzed for pH, organic carbon (C), total nitrogen (N), C/N ratio, available phosphorus (P), exchangeable cations (Ca, Mg, K, Na), and Cation Exchange Capacity (CEC). Results showed age-dependent recovery. The 10 year sites had pH (5.03) closest to forest (4.96), while younger sites remained more acidic (4.80-4.88). Organic C (7.68%) and total N (0.15%) increased with age but were still below forest levels (16.99% and 0.37%). The C/N ratio distinguished recovery stages: 3-6 year sites showed rapid turnover (C/N=5.00-7.33), whereas 10 year sites resembled forest (53.67). Available P peaked at 6 years (21.38 mg/kg) before declining, and exchangeable cations showed variable patterns. CEC peaked in 10 year sites (86.30 cmol/100 g), exceeding forest (49.87 cmol/100 g), indicating improved nutrient retention. Correlation with forest soils was strong (R²=0.87). These results demonstrate substantial recovery of soil chemical properties within a decade, though long-term organic matter accumulation and balanced nutrient management remain essential for full ecosystem restoration.